Grading vs. scientific publications: Data envelopment analysis as a method of teacher assessment - Gomez Alvarado, H. (2016)
Teacher' assessment comprises a basic element for the development of academy. In fact, there are many factors that can influence it. Therefore, it is important to consider the way in which certain factors provide information about the performance and efficiency of university professors. Our proposal consists of using data envelopment analysis with the aim of showing how one can adequately estimate the parameters of assessment and grading and see how this compares with scientific publications. We worked with data of 60 professors from two universities. The results show that it is possible to identify barriers to efficiency, and that the parameters can be considered individually or collectively to determine a just value for teacher assessment. © 2016 IEEE.